Analytical and numerical approaches to predict the flow characteristics of a magnetorheological fluid in rotational symmetric cross sections - Rösel, Sebastian; Merklein, Marion; Grüner, Martin (Key Engineering Materials, 2012)
For a better understanding of the hydroforming process using magnetorheological fluids as a medium it is necessary to gain basic information for an analytical and numerical description of the fluid behaviour under process relevant conditions. Therefore an experimental setup is build up, which consists of a pressure chamber and a rotational symmetric outlet. Different parameters like feed rate and magnetic flux density are varied. Afterwards an analytical approach and a numerical model are developed. To get the relevant material input data for the fluid description an additional numerical simulation of the created magnetic flux density with flux lines perpendicular to the symmetry line of the outlet is performed. The leakage rates, which are observed for the experiments, are compared to the analytically calculated ones and to the results of the numerical simulation. © (2012) Trans Tech Publications.
LFT Import::2019-07-29 (1803)
Keywords: Active fluid media; Hydroforming; Magnetorheological fluid (MR-Fluid); Sheet metal forming

Analytic Methods for the Calculation of the Heat Transfer Coefficient - Merklein, Marion; Wieland, Michael; Stöhr, Thomas; Lechler, Jürgen; Grüner, Martin (International Review of Mechanical Engineering, 2010)
In the product development cycle numerical simulations are commonly used for the process layout. In case of hot stamping the process layout gets quite complex because material's thermal and mechanical properties have to be taken into account. Hot stamping can be explained as forming and quenching in one process step and therefore the knowledge of thermal properties is indispensable to fulfill the opposing requirements of a good heat flux with respect to a good energy balance of the tool. A description of this energy exchange between the hot blank and the tool is given by the heat transfer coefficient. The determination of the heat flux under process relevant conditions for hot stamping is influenced by several variables. Within the scope of this work, these different variables are compared using two analytical methods to calculate the heat transfer coefficient based on the same measurement data. Furthermore the advantage of these analytical methods and the possibility of improvement is shown up. At least a validation of the calculated heat transfer coefficients by simulation is presented. Copyright © 2010 Praise Worthy Prize S.r.l. - All rights reserved.
LFT Import::2019-07-29 (224)
Keywords: Heat transfer coefficient; Hot stamping

Basic experimental and numerical investigations on chip pressing - Grüner, Martin; Merklein, Marion (Key Engineering Materials, 2013)
Aluminium alloys show a great potential for lightweight constructions due to their high strength and low density but the production of this material is very energy consuming. Also the recycling of aluminium alloys, e.g. chips from the milling process, shows different challenges. Beside contamination by cooling lubricant and oxidation of the surface of the chips the melting and rolling process for new semi finish products needs a high amount of energy. TEKKAYA shows a new approach for recycling of aluminium alloy chips by an extrusion process at elevated temperatures producing different kinds of profiles. A new idea is the production of components directly out of chips using severe plastic deformation for joining of the chips similar to the accumulative roll bonding process in sheet metal forming. In a first approach aluminium alloy chips out of a milling process were uniaxial compressed with different loads inside an axisymmetric tool installed in a universal testing machine. The compressed chip disks subsequently were tested with two experiments to gain information on their stability. First experiment is a disk compression test with the disk standing on its cylindrical surface, giving information on the stability perpendicular to the compression direction. Second experiment is a stacked disk compression test with three disks to investigate the stability parallel to compression direction. During all three tests force and displacement values are recorded by the universal testing machine. These data are also processed to calculate or identify input parameters for the numerical investigations. For numerical simulation ABAQUS in conjunction with the Drucker-Prager-Cap material model, which is often used for sintering processes, seems to be a good choice. By numerical simulation of the experiments and comparison with the experiments input parameters for the material model can be identified showing good accordance. This material model will be used in future numerical investigations of an extrusion process to identify tool geometries leading to high strains inside the material and by this to an increased stability of the parts. Copyright © 2013 Trans Tech Publications Ltd.
LFT Import::2019-07-29 (1890)
Keywords: Aluminum alloys; Chip pressing; Drucker-prager-cap; Recycling

Blank hydroforming using granular material as medium - investigations on leakage - Grüner, Martin; Gnibl, Tobias; Merklein, Marion (Procedia Engineering, 2014)
LFT Import::2019-07-29 (2032)
Keywords: Granular material; Hydroforming; Leakage

Comparison of numerical simulation and measurement of shear test and uniaxial compression test to verify material model for granular material used as medium for hydroforming - Grüner, Martin; Merklein, Marion (Proc. 5th International Conference on Advances in Production Engineering, 2010)
LFT Import::2019-08-05 (494)

Consideration of elastic tool deformation in numerical simulation of hydrofroming with granular material used as a medium - Grüner, Martin; Merklein, Marion (Key Engineering Materials, 2011)
LFT Import::2019-07-29 (1653)

Determination of friction coefficients in deep drawing by modification of Siebel's formula for calculation of ideal drawing force - Grüner, Martin; Merklein, Marion (Production Engineering, 2014)
LFT Import::2019-07-29 (2031)

Einfluss der Fließkurve auf den Rohrbiegeradius - Merklein, Marion; Vatter, Peter; Plettke, Raoul; Grüner, Martin (wt Werkstattstechnik - Online, 2012)
LFT Import::2019-07-29 (1816)

Enhancing Process Limits of Blank Hydroforming - Merklein, Marion; Grüner, Martin; Rösel, Sebastian (Internationale Konferenz „Hydroumformung von Blechen, Rohren und Profilen“, 2012)
LFT Import::2019-08-05 (1813)

Experimental Determination of Yield Loci for Magnesium Alloy AZ31 under Biaxial Tensile Stress Conditions at Elevated Temperatures - Geiger, Manfred; Merklein, Marion; Hußnätter, Wolfgang; Grüner, Martin (Production Engineering, 2008)
The finite element analysis (FEA) has become one of the most relevant and most important tools in fields of sheet metal forming for designing processes and dimensioning parts. However, reliability and quality of the numerical results strongly depend on the whole FE-model and especially on the modeling of the material behavior, which shows wide impact on calculated stresses and strains of sheet metal parts. Therefore, the experimental determination of characteristic material data concerning anisotropic and temperature-effects is essential. In this paper the influence of temperature on the yielding and the hardening behavior of the magnesium sheet metal alloy AZ31 are investigated for different uniaxial and biaxial stress conditions. For that purpose an experimental setup has been developed at the Chair of Manufacturing Technology (LFT) which enables biaxial tensile testing of sheet metal. Yield loci of AZ31 are determined as a function of temperature and they are based on solely measurement data of the forming process itself. © German Academic Society for Production Engineering (WGP) 2008.
LFT Import::2019-07-29 (294)
Keywords: Computer aided engineering; Material characterization; Yield locus diagram

FE-Simulation of the heat transfer by defined cooling conditions during the hot stamping process - Svec, Thomas; Grüner, Martin; Merklein, Marion (Key Engineering Materials, 2011)
LFT Import::2019-07-29 (1642)
Keywords: Heat transfer; Hot stamping; Numerical simulation; Tailored tempering

Fügen durch Umformen - Das Spannungsfeld zwischen Umform- und Fügetechnik - Merklein, Marion; Grüner, Martin; Müller, Martin; Wieland, Michael (Effiziente Fertigung von Hochleistungsverbundsystemen - Proc. 18. Paderborner Symposium Fügetechnik, 2013)
LFT Import::2019-08-05 (2009)

Hochdruck-Blechumformung mit formlos festen Stoffen als Wirkmedium - Grüner, Martin (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)
Using small ceramic spheres as forming medium for blank hydroforming processes allows combining benefits of hydroforming and warm forming of ultra high strength steel. Especially the advantageous leakage behavior of granular material compared to gases and fluids allows a significant reduction of blankholder forces and thereby an increase in moldin

Influences on the Molding in Hydroforming Using Granular Material as a Medium - Grüner, Martin; Merklein, Marion (AIP Conference Proceedings Volume 1383 - The 8th International Conference and Workshop on Numerical Simulation of 3D Sheet Metal Forming Processes (NUMISHEET 2011), 2011)
The need of lightweight construction for the body in white of modern cars increases due to legal restrictions of CO2 emissions and the passenger s wishes of safety and low fuel consumption. On e approach of lightweight construction is the use of high and ultra high strength steel, to reduce the weight of the single parts, another approach is the use of modern forming technologies, e.g. hydroforming with the possibility to create undercuts, to produce complex parts and thus to reduce the number of parts, the number of joining operations and the weight. The mentioned ultra high strength steels show a poor formability at room temperature and the necessary process forces are high compared to standard deep drawings teels. Warmforming operations can help to reduce the process forces and to increase formability [1]. To combine the benefits of warm forming and hydroforming new forming media are necessary to overcome the problem of temperature stability of fluids, which is limited to about 350 °C [2]. Beside gases, which tend to leakage and which are highly compressible, granular material like small ceramic beads can be used as a forming medium. First results of forming operations using this medium were presented in [3]. The experimental tool used for those tests pressurizes the medium by a punch. To divide the effects caused by temperature and steel grade from the other effects experiments were carried out at room temperature using the well know n deep drawing steel DC04. Influences of the ceramic beads diameter, the number of repetitions, the punch geometry as the punch position, determining the volume of media, on the forming are presented. © 2011 American Institute of Physics.
LFT Import::2019-08-05 (1757)
Keywords: Elevated temperatures; Granular material; Hydroforming

Mechanical Behaviour of Ceramic Beads Used as Medium for Hydroforming at Elevated Temperatures - Grüner, Martin; Merklein, Marion (Key Engineering Materials, 2009)
The need of light weight construction for high efficient vehicles leads to the use of new materials like aluminium and magnesium alloys or high strength and ultra high strength steels. At elevated temperatures the formability of steel increases as the flow stresses decrease. Forming high complex geometries like chassis components or components of the exhaust system of vehicles can be done by hydroforming. The hydroforming process by oils is limited to temperatures of approximately 300 °C and brings disadvantages of possible leakage and fouling. Using granular material like small ceramic beads as medium could be an approach for hydroforming of ultra high strength steels like MS-W1200 and CP-W800 at temperatures up to 600 °C. The material properties of granular material are in some points similar to solid bodies, in other points similar to liquids. For understanding and simulation of the behaviour of the medium a basic characterisation of ceramic beads with different ball diameters is necessary. Powder mechanics and soil engineering give ideas for experimental setups. For the conversion of these approaches on the one hand the behaviour of the ceramic beads itself has to be characterized, on the other hand the contact between a blank and the beads have to be investigated. For the tests three different kinds of spheres with a diameter between 63 microns and 850 microns are used. In unidirectional compression test compressibility, pressure distribution in compression direction and transversal compression direction and the effect of bead fracture are investigated. The tests are carried out at different compression velocities and for multiple compressions. For determination of friction coefficients between blank and beads and determination of shear stress in bulk under compression a modified Jenike-Shear-Cell for use in universal testing machines with the possibility of hydraulic compression of the beads is built up. The gained data can be used for material modelling in ABAQUS using Mohr-Coulomb or Drucker-Prager model. © (2009) Trans Tech Publications, Switzerland.
LFT Import::2019-07-29 (301)
Keywords: Elevated temperatures; Granular material; Hydroforming

Methods for Determination of Residual Stress of a Formed Plate using Laser Ablation, Wire EDM and Milling - Lamsa, Janne; Mantyjarvi, Karl; Jarvenpaa, Antti; Grüner, Martin; Merklein, Marion; Karjalainen, Jussi A. (Key Engineering Materials, 2011)
In this work laser ablation was used for the determination of residual stress of a formed plate. Manufacturing processes, like bending, create residual stresses in the product and those can be very disadvantageous for fatigue durability. Residual stresses that are generated during the manufacturing of products can cause distortions, dimensional errors or can even break the products. The research material was ultra-high-strength steel (UHSS) with a yield strength of 1100 MPa. Specimens with a 90 degree bent angle were made by air bending using a press brake. Air bending causes variable residual stress patterns in the cross section of the material. The residual stresses of the formed area were determined by removing material and measuring strains caused by the release of stresses. A slot with the width of 1 mm has been manufactured parallel to the edge, both on the outer and on the inner side of the bend. True residual stress distribution can be calculated from the measured strains. A pumped 1064 nm Nd:YVO 4 ablation laser, whose pulse length is 90 ns, was used for the removal of material. This process creates a negligible heat affected zone (HAZ) and laser ablation doesn't increase stresses in the specimen. The results were compared with those obtained when slots were produced by milling and wire-EDM, as well as with the stress values measured by X-ray diffraction. © (2011) Trans Tech Publications.
LFT Import::2019-07-29 (1654)
Keywords: Bending; Laser ablation; Residual stress

Numerical Simulation of Hydroforming at Elevated Temperatures with Granular Material Used as Medium Compared to the Real Part Geometry - Grüner, Martin; Merklein, Marion (International Journal of Material Forming, 2010)
LFT Import::2019-07-29 (299)

Prototype Manufacturing of Helical Needles for Suture in Deep Wound Cavities - Plettke, Raoul; Vipavc, Daniel; Grüner, Martin; Hagenah, Hinnerk; Merklein, Marion (Proc. 1st Int.Conf. Design and Processes for medical devices PROMED, 2012)
LFT Import::2019-08-05 (1837)

The influence of the annealing process in the fabrication of helical needles for the suture in deep wound cavities - Plettke, Raoul; Vipavc, Daniel; Grüner, Martin; Hagenah, Hinnerk; Merklein, Marion (International Journal of Computer Integrated Manufacturing, 2014)
The standard procedure of a surgical suture can be very difficult to perform in deep-wound cavities because the available space is not enough to perform the complicated movements required for the knot or to handle the needle. To improve this situation a new kind of hollow, helical needle was developed and filed for patent. To ensure the manufacturability of this kind of needle, a prototype and a prototypical tool were designed and tested. As a prototypical basis, commercially available cannulas were selected. Coil winding was used as a forming process to bring the cannula into the helical form. The material properties of the surgical steel and the work hardening that the semi-finished products underwent lead to challenges for the forming process. The limitations of springback and low formability reduce the possible radius of the helix. Therefore, a soft annealing of the cannula was investigated. However, in surgical needles, stiffness is of great importance. Since hardening by quenching is not possible, annealing parameters were chosen to retain the necessary stiffness. Based on the data obtained from tests of annealing parameters, four final geometries of helical needles were designed and first prototypes were manufactured. © 2013 Taylor & Francis.
LFT Import::2019-07-29 (1901)
Keywords: annealing; case study; deep wound; helical needle; suture; winding